The Influence of Raw Materials and Direct Labor Costs on Profit Margin Ratio in UMKM Agan Cibinong, Bogor Regency - Yuppy Triwidatin (PT FORMOSA CENDEKIA GLOBAL, 2022)
Micro, Small and Medium Enterprises or known as UMKM have many roles in eradicating poverty, reducing unemployment, and increasing people's income so that they can be independent in supporting their economy. UMKM actors must be able to develop and survive in line with intense business competition. The ability to compete in trade is important so that the Indonesian economy remains strong, especially in the face of the Asean Economic Community (AEC). Therefore, the government continues to strive so that UMKM in various regions can develop so as to support the economy of small communities by providing various facilities both in terms of funding, marketing, licensing and other supporting facilities. The presence of the industrial revolution 4.0 has the impact of intense competition, UMKM must be able to overcome this challenge creatively, product innovation, marketing, product packaging, human resource development and technology. The UMKM empowerment strategy can be pursued through the role of the Government in issuing fiscal and non-fiscal policies, the role of universities in carrying out services to educate and prosper the community and the role of stakeholders in encouraging UMKM to be more independent and innovative.